Dependent self-employment: workers between employment and self-employment in the UK - René Böheim; Ulrike Mühlberger (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
Analysing the British Labour Force Survey, we highlight that dependent self-employed workers constitute a group distinct from both employees and independent self-employed workers in the labour market group. Dependent self-employed workers show characteristics of a more volatile labour market attachment than employed or self-employed workers. We provide empirical evidence that dependent self-employed workers are rather pushed than pulled into this labour market status, making dependent self-employment an example of 'necessity' rather than 'opportunity' entrepreneurship. Although data limitations only allow a limited longitudinal analysis, we provide evidence that the majority of dependent self-employed workers remain in the labour market in the short run - either as self-employed or employed - and that only few leave the labour market. In addition, dependent self-employment does not create jobs for others; in our data, dependent self-employed individuals stop being dependent and self-employed because they increase their customer base or return to paid employment.
Keywords: K31; J21; J22; 330; Scheinselbständige; berufliche Selbständigkeit; Berufsverlauf; Arbeitsmarktrisiko; Arbeitsrecht; Großbritannien